A compensatory model to understand dysfunctional personality traits in problematic gaming: The role of vulnerable narcissism. (1st July 2020) - Di Blasi, Maria; Giardina, Alessandro; Lo Coco, Gianluca; Giordano, Cecilia; Billieux, Joel; Schimmenti, Adriano
Highlights: Vulnerable (but not grandiose) narcissism predicts problematic gaming. Emotion dysregulation-escapism link mediates this association. Vulnerable narcissism appears to promote gaming as a coping mechanism. Emotion dysregulation may be an important target for treatment of problematic gaming. Abstract: According to a "compensatory perspective", this study aimed to examine the role of narcissism (both vulnerable and grandiose) in the relationship between emotion dysregulation, escapism motivation to play, and problematic gaming. In a sample of 405 World of Warcraft players, we tested a multiple mediation model in which the relationship between vulnerable/grandiose narcissism and problematic gaming was mediated by emotion dysregulation and escapism. Results showed that the model for vulnerable (but not grandiose) narcissism fitted the data very well. This study adds novel insight to our understanding of the mechanisms that support problematic gaming, suggesting that the emotion dysregulation-escapism connection can be boosted by the presence of vulnerable narcissistic traits. Consequently, clinicians should consider the relevance of vulnerable narcissistic personality traits in persons who display a problematic engagement with massively multiplayer online role-playing games.